A New Flavone from Erythrina suberosa, its Biological Screening and Application as pH Indicator - Pathan, Mohd Arif Khan; Ahad, Abdul; Farooqui, Mazahar (Orbital: The Electronic Journal of Chemistry, 2019)
A new flavone is isolated, characterized and its pH indicator property is studied for titration between strong/weak acids and bases. Flavone (Z)-3-hydroxy-2-(4-hydroxy-3-methoxyphenyl)-5-(isopentyloxy)-7-methoxy-6-(2-methylpent-1-en-1-yl) chromenylium chloride has been isolated by extracting ether and methanol. Compound is separated using column chromatography and identified with the help of spectroscopic techniques such as mass, 1HNMR, IR and UV. Compound is also screened for its antibacterial and anti-fungal activity from the flower extract of Erythrina suberosa. Activity of the isolated compound is observed for E Coli bacteria as a gram-negative organism. The compound shows significant color change in acidic and alkaline medium and its potential as pH indicator is encouraging. DOI: http://dx.doi.org/10.17807/orbital.v11i5.1150